APPLICATION OF HEALTH PROTOCOL IN PANDEMIC AGE IN 8 YEARS OLD CHILDREN IN RT 55 RW 11 DUSUN BAYATREJO, WRINGINPITU VILLAGE, TEGAL DLIMO DISTRICT - Amalia Nurul Khoiriyah; Harwanti Noviandari; Ahmad Sulthoni (International Jurnal of Education Schoolars, 2020)
This study aims to provide an understanding and to provide an explanation regarding the importance of implementing health protocols for children aged 8 years in the RT 55 RW 11 hamlet Bayatrejo, Wringinpitu Village, Tegaldlimo District. Health protocols are very important. The importance of providing education and application of health protocols to increase understanding for children so as to reduce the level of spread of COVID-19. Public awareness in complying with health protocols also affects the current conditions. The lack of public awareness has resulted in more and more people being affected by COVID-19, day by day the number of cases of COVID-19 is increasing, especially children who are vulnerable to the virus and do not understand the importance of health protocols. The type and approach in this study is a qualitative descriptive analysis method, which is to analyze, describe, and summarize in various conditions, situations from various data collected in the form of interviews or observations about the problems studied that occur in the field. So that it can produce data that is appropriate and in accordance with the objectives of this study. In this study, the researchers determined the number of subjects to be studied, namely the total number of children aged 8 years there were 10 children, then the researchers determined the subjects to be 2 children and 1 mother from one of the children. The participants of this study were 2 children aged 8 years and 1 mother of one of these children. The results of this study indicate that the children have implemented health protocols in their daily activities well, with self-awareness and role modeling from parents who have been given as well as social attributions to themselves. Children in the RT/RW 55/11 hamlet Bayatrejo, Wringinpitu Village, Tegaldlmo District have complied with health protocols, so that children can understand the importance of health protocols in order to break the chain of spread of covid-19, which until now there are still many victims affected by the COVID-19 virus. 19 of these. And parents are very influential in setting an example for their children, so they can provide a behavioral stimulus for children to implement health protocols properly